Consumer involvement with corporate ads vs product ads: a cross-national study. Issue 2 (27th September 2019) - Ashraf, Rohail; Albert, Noel; Merunka, Dwight; Khan, Muhammad Asif
Abstract : Purpose: Increasing consumer skepticism of corporate behavior has led companies to actively manage and advertise their corporate brands. However, it remains unclear how receptive consumers across different markets are to such efforts. The purpose of this paper is to demonstrate differences and similarities between corporate and product advertising by examining consumer ad involvement (AI) levels (a motivational state activated by the personal relevance of stimuli) and its antecedents and consequences for these ad types across two markets with varying degrees of economic development. Design/methodology/approach: Using a 2 (ad type: corporate vs product) × 2 (market type: developed vs emerging) between-subject experimental design, the study was conducted in two markets with varying degrees of economic development, specifically, the USA ( n =285) and Pakistan ( n =311). Findings: Results show that consumer involvement with corporate ads varies for developed (USA: high) and emerging (Pakistan: low) markets but that it remains the same for product ads across markets. Developed market consumers tend to be as involved with corporate ads as they are with product ads, whereas emerging market consumers are more involved with product ads than with corporate ads. Aside from differences in involvement levels, the findings demonstrate substantial similarities in the antecedents and consequences of consumer involvement for both ad (corporate vs product) and market (developed vs emerging) types. Practical implications: With advertising and communication campaigns increasingly being standardized across different markets, this study demonstrates that corporate messages do not function similar as product messages across markets. For effective corporate campaigns, ad designs should fit with the motivation levels of the target consumers across markets. Originality/value: This study demonstrates the differences and similarities between corporate and product AI across a developed and an emerging market.